A coordinate-free approach to instantaneous kinematics of two rigid objects with rolling contact and its implications for trajectory planning - Cui, Lei; Dai, Jian (IEEE Press, 2009)
This paper adopts a coordinate-free approach to investigate the kinematics of rigid bodies with rolling contact. A new equation of angular velocity of the moving body is derived in terms of the magnitude of rolling velocity and two sets of geometric invariants belonging to the respective contact curves. This new formulation can be differentiated up to any order. Furthermore, qualitative information about trajectory planning can be deduced from this equation if the characteristics of rolling objects and the motion are taken into consideration.